In Reply. (17th June 2020) - Raber, Inbar; Peters, Mary Linton; Asnani, Aarti
Abstract : In response to the letter to the editor by Lestuzzi et al., results of a recently published article on fluoropyrimidine‐associated cardiotoxity are clarified.